PERILAKU SOSIAL PEKERJA SEKS KOMERSIAL (PSK)DI DUNIA PELACURAN - Hidayah, Siti Nurul (IJTIMAIYA: Journal of Social Science and Teaching, 2018)
In this modern era the world of prostitution has always been a social issue that appeals to everyone in the neighborhood of rural and urban communities. This is what the world calls in a world of prostitution that includes behavior in the use of things, the world of competition, and the language used for use. While this research uses descriptive qualitative approach, using Interpretative paradigm that focuses more on the paradigm of phenomenology, etnosaince, and ednometodologi. Technique of writing data in this research use language, interview, and study of documentation. The results of the study show that (1) Social behavior of prostitutes in the use of objects such as condoms are very important in the world to serve its customers during sexual intercourse. Without condoms, CSWs are afraid to serve their customers. The use of condoms for referrals for CSWs to avoid the condition of infectious diseases. (2) In the social behavior of prostitutes in the prostitution world there is competition between fellow CSWs in different lokalisasion, the competition is not only done physically, by displaying a captivating appearance, but here more on the mystical rivalry, using the help of shamans, very closely with the CSWs. Competition is done to burden other CSWs or to attract customers. (3) The language of prostitutes for use in prostitution is different from the prostitution. The language that prostitutes in the world of prostitution is very dirty, hard, and often do curses.                                                                                                                      Keywords: social behavior, commercial sex workers, prostitution